Solutions of Nonlinear Delay Differential Equations by Daftardar-Jafari Method - (:unkn) unknown (My University, 2018)
In this paper efficiency of Daftardar-Jafari Method (DJM) is compared with some other iterativemethods, Adomian Decomposition Method (ADM) and Differential Transformation Method (DTM) in obtainingapproximate solutions of nonlinear differential equations with proportional delay. As all these 3 methods considersolutions in series form it is important to know about their convergence rate to the exact solution. We analyse then-term approximation of the series solutions of these 3 methods with 3 numerical examples to see if DJM is as goodas ADM and DTM in solving nonlinear delay differential equations. The results show DJM approaches to the exactsolution with fewer iterations compared with ADM and DTM